THE EFFECT OF CUSTOMER CO-CREATION AND CUSTOMER EXPERIENCE ON ELECTRONIC WORD OF MOUTH (EWOM) THROUGH CUSTOMER SATISFACTION ON SHARIA INDONESIAN BANK IN MEDAN CITY - Rizky Amalia Nasution; Amrin Fauzi; Arlina Nurbaity Lubis (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The banking industry is currently facing many challenges because it is considered very competitive, complex and dynamic. In getting new customers, banks must make changes that can attract customers, one of which is marketing through eWOM. Positive eWOM is created when banks provide the best service for customers. In its goal of creating positive eWOM, banks must improve customer experience and customer satisfaction, besides that customer co-creation is also considered as an effort to increase competitiveness and create positive eWOM. This study aimed to analyze and determine the effect of customer co-creation, and customer experience on electronic word of mouth (eWOM) through customer satisfaction on Bank Syariah Indonesia customers in Medan City. The population in this study were BSI customers who were Twitter users as many as 110 people. The sampling method uses non-probability techniques with purposive sampling. The data analysis method uses Structural Equation Modeling- Partial Least Squares (SEM-PLS). The results showed that customer co-creation has a positive and significant effect on eWOM, customer experience has a negative and insignificant effect on eWOM, customer co-creation has a positive and significant effect on customer satisfaction, customer experience has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on eWOM, customer co-creation has a positive and significant effect on eWOM through customer satisfaction, customer experience has a positive and significant effect on eWOM through customer satisfaction.